A Matlab Algorithm for the Resolution of Fourth Degree Equations - Donato, Alessia (Journal of Mathematical Economics and Finance; Vol 3 No 2(5) (2017): JMEF Volume III, Issue 2(5), Winter 2017DO - 10.14505/jmef.v3.2(5).01, 2018)
In this article,  we propose  an algorithm for the resolution of fourth degree equations,  explicitly showing the solution method used, and we compare the results ob- tained with the Matlab “root” command.